2021
DOI: 10.1093/icesjms/fsab190
|View full text |Cite
|
Sign up to set email alerts
|

Temporal fluctuations in zooplankton size, abundance, and taxonomic composition since 1995 in the North Western Mediterranean Sea

Abstract: In the Gulf of Lions, small pelagic fish have shown reduced body size and body condition after 2007 that would result from changes in zooplankton community. We therefore examined zooplankton density, body size, and taxonomic composition at the closest long-term monitoring station (1995–2019): the coastal Point-B. To cover a broader spectrum of zooplankton community, samples obtained from two nets, the WP2 (200 µm mesh size) and the Regent (690 µm), were analysed with the imaging Zooscan method. One important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 91 publications
(124 reference statements)
3
18
0
Order By: Relevance
“…Although our results show a strong difference in the abundance of P. atlanticum in the two years studied, longer time series would be necessary to confirm the high interannual variability that has been described for gelatinous zooplankton in the Mediterranean ( García-Comas et al ., 2011 ; Fullgrabe et al ., 2020 ; Feuilloley et al ., 2021 ). This high variability has been related to the winter environmental conditions, which cause mixing of the water column and the input of nutrients to the surface waters, ultimately modulating the phytoplankton bloom ( García-Comas et al ., 2011 ; Fullgrabe et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results show a strong difference in the abundance of P. atlanticum in the two years studied, longer time series would be necessary to confirm the high interannual variability that has been described for gelatinous zooplankton in the Mediterranean ( García-Comas et al ., 2011 ; Fullgrabe et al ., 2020 ; Feuilloley et al ., 2021 ). This high variability has been related to the winter environmental conditions, which cause mixing of the water column and the input of nutrients to the surface waters, ultimately modulating the phytoplankton bloom ( García-Comas et al ., 2011 ; Fullgrabe et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out on gelatinous zooplankton in the NW Mediterranean have shown high spatial variability closely linked to oceanographic dynamics and water mass structure ( Guerrero et al ., 2016 ; Sabatés et al ., 2018 ). At a temporal scale, high interannual variability has been reported in abundance and species composition ( Licandro and Ibanez, 2000 ; Guerrero et al ., 2018b ; Feuilloley et al ., 2021 ), but there is no clear consensus on long-term trends ( Molinero et al ., 2005 ; García-Comas et al ., 2011 ; Licandro et al ., 2012 ; Guerrero et al ., 2018a ). Studies on P. atlanticum in the Mediterranean are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The model also improved the accuracy of detecting rare taxa by an average of 4.02% and has the potential to be included in autonomous underwater vehicles for real-time identification and plankton ecosystem observation . The model proposed by Gorsky et al ZooScan with ZooProcess was successfully implemented in the identification and estimation of ZP abundance in the bay of Villefranche-sur-Mer, France . This shows that ML algorithms are a potential tool not only for the identification of ZP but also used to solving ecological problems.…”
Section: Biological Oceanographymentioning
confidence: 93%
“… 119 The model proposed by Gorsky et al 104 ZooScan with ZooProcess was successfully implemented in the identification and estimation of ZP abundance in the bay of Villefranche-sur-Mer, France. 120 This shows that ML algorithms are a potential tool not only for the identification of ZP but also used to solving ecological problems. Still, few improvements are required in this field to achieve full automation to detect rare taxa and morphologically similar species.…”
Section: Biological Oceanographymentioning
confidence: 99%
“…Zooplankton communities and their quality as food supply for predators were not assessed. Feuilloley et al (2022), using a long time series of zooplankton observations in the northwestern Mediterranean, showed that changes in zooplankton composition, size, and density may impact higher trophic levels, such as the fitness of small pelagic fish. Results should be considered cautiously as both plastic and zooplankton were averaged over 6 months in the same year (June-November 2014).…”
Section: Limitsmentioning
confidence: 99%